2019
DOI: 10.1200/jco.2019.37.15_suppl.1549
|View full text |Cite
|
Sign up to set email alerts
|

Contralateral breast cancer risk according to first breast cancer characteristics among United States women from 1992 to 2015.

Abstract: 1549 Background: After recent advances in breast cancer treatment and increasing uptake of contralateral prophylactic mastectomies, estimates of contralateral breast cancer (CBC) risk by year of diagnosis and other patient characteristics are needed to help inform decision making. Methods: We estimated CBC risk in 399,032 1-year survivors of a first primary breast cancer (stage I-III) in the US Surveillance, Epidemiology, and End Results Database (1992-2015). CBC was defined as an invasive second breast cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Women with BC carry a high risk for contralateral breast cancer (CBC), identified by mammography in between 1% and 4% of women. 45,46 Ultrasound may be used to search for additional CBC. In a recent retrospective analysis, Leblond et al 47 found that ultrasound was positive in 76 of 360 patients with mammographically unilateral cancer; biopsy confirmed cancer in 11 of 76 (positive predictive value, 14.5%), for an additional CBC detection rate of 11 (3.1%) of 360 patients.…”
Section: Imaging To Identify Additional Bc In the Opposite Breastmentioning
confidence: 99%
“…Women with BC carry a high risk for contralateral breast cancer (CBC), identified by mammography in between 1% and 4% of women. 45,46 Ultrasound may be used to search for additional CBC. In a recent retrospective analysis, Leblond et al 47 found that ultrasound was positive in 76 of 360 patients with mammographically unilateral cancer; biopsy confirmed cancer in 11 of 76 (positive predictive value, 14.5%), for an additional CBC detection rate of 11 (3.1%) of 360 patients.…”
Section: Imaging To Identify Additional Bc In the Opposite Breastmentioning
confidence: 99%
“…The rate at which patients relapse elsewhere in the breast or regionally should be similar to the risk factors for a CBC, which typically include biological risk groups, such as lobular histology, lack of an estrogen receptor, a higher proliferation index, or a history of receipt of radiation therapy. Conversely, systemic therapies, such as endocrine-, chemo-, and Her2-targeted therapies are protective agents [87,88]. Therefore, the logical conclusion is to select low-risk patients for partial-breast treatments where the risk of relapse in the remaining glandular tissue and regional lymph nodes is either negligible or is adequately treated by adjuvant systemic therapy [62,89].…”
Section: Resultsmentioning
confidence: 99%
“…It is well-documented that women with breast cancer have a greater risk of developing contralateral breast cancer (CBC), 5 with a 5-year cumulative incidence between 1% and 1.8%, depending on tumor and treatment characteristics. 6 This study aimed to evaluate the value of mammography with breast and axillary ultrasound undertaken before adjuvant radiotherapy in patients with conservatively managed invasive carcinoma and/or in situ carcinoma of the breast, to address its value regarding the contralateral breast and axilla, and to determine whether there is any group of patients with an increased risk for CBC where routine PLI should not be discarded.…”
Section: Introductionmentioning
confidence: 99%